Crystal structure and fluorescence analysis of alkaline thermostable xylanase from bacillus sp (NCL 87-6-10) - Satyanarayana, L.; Gaikwad, Sushama M.; Balkrishnan, H.; Suresh, C. G. (Protein and Peptide Letters, 2013)
Structural information deduced from the new crystal form of xylanase from Bacillus sp (NCL 87-6-10) (ATBXYL-C) helped us to identify the active site and interpret the stability of the enzyme. The analysis of the tetragonal crystal structure of ATBXYL-C with a bound and cleaved xylotriose revealed the two glutamic acid residues in the structure that could act as nucleophile (Glu94) and base (Glu184) in the enzyme activity and also the tryptophan residues interacting with the substrate. The cleavage of xylotriose in the crystal showed xylobiose to be the major product. Intrinsic fluorescence of the enzyme showed the presence of tryptophans in partially exposed to the solvent at the active site and surface tryptophans in electropositive environment. The titration experiments with xylobiose and xylotriose revealed slightly enhanced preference for longer chain X3 compared with X2. The crystal structure also account for some of the factors, such as increased number of ionic interactions and additional interactions at the N-terminus, which contributed to increased alkalophilicity and thermostability of the enzyme.
Keywords: active site residues; Alkaline thermophile Bacillus xylanase (ATBXYL-C); fluorescence studies; three-dimensional structure